Particular aspects of environmental impact of potentially risk elements from airborne particulate matter - J. Száková; J. Sysalová; P. Tlustoš (Plant, Soil and Environment, 2005)
Two simple experiments were carried out to demonstrate two possible ways of environmental impact of element contents in airborne particulate matter. In the first part of the experiment, the response of three rural dust samples applied into the soil were assessed in pot experiment to observe uptake of As, Cd, Pb, and Zn by aboveground biomass of oat (Avena sativa L.). Although the element contents in dust samples exceeded significantly total element contents in soil, the element content in plants was not affected by single-rate soil amendment with rural dust sample. Soil sorption capacity and neutral pH of the experimental soil (7.0) was sufficient for immobilization of the elements. However, potentially mobilizable portions (0.005 mol/l DTPA extractable) of elements significantly increased (Cd by 116%, Pb by 39%, Zn by 50%) in the treated soil, which suggests a possible release of these elements in long-term horizon. On the contrary, high percentages of potentially toxic elements (Cd, Zn, Ni) in the most mobile (exchangeable) fractions were determined in the second part of investigation in two urban dust samples collected in Prague Letná automobile tunnel, and Prague subway station Museum. These results suggest possible direct impact of mobile, and thus potentially bio-available, element fractions on human environment. The results of both particular experiments cannot give complete information concerning behavior of harmful pollutants in airborne particulate matter and their influence on human health. They can however indicate two of possible ways of environmental pollution with this material. Yet, it would require a more detailed investigation in future.